Nuclear Medicine and Artificial Intelligence: Best Practices for Algorithm Development - Bradshaw, Tyler J; Boellaard, Ronald; Dutta, Joyita; Jha, Abhinav K; Jacobs, Paul; Li, Quanzheng; Liu, Chi; Sitek, Arkadiusz; Saboury, Babak; Scott, Peter J H; Slomka, Piotr J; Sunderland, John J; et al. (The Journal of nuclear medicine (1978), 2022)
The nuclear medicine field has seen a rapid expansion of academic and commercial interest in developing artificial intelligence (AI) algorithms. Users and developers can avoid some of the pitfalls of AI by recognizing and following best practices in AI algorithm development. In this article, recommendations on technical best practices for developing AI algorithms in nuclear medicine are provided, beginning with general recommendations and then continuing with descriptions of how one might practice these principles for specific topics within nuclear medicine. This report was produced by the AI Task Force of the Society of Nuclear Medicine and Molecular Imaging.